Necrotizing Fasciitis of Lower Limb: A Surgical Emergency - Zafar Iqbal Malik, M Naeem Ashraf, Naeem Akhtar, M. Kamran Afzal, Munawer Latif (Journal of Rawalpindi Medical College, 2012)
mortality in patients presenting with Necrotizing Fasciitis. Methods: In this descriptive study, patients with Necrotizing Fasciitis were included. After resuscitation, the patients underwent emergency exploration and aggressive surgical debridement. Post-operatively, the patients were managed with broad spectrum antibiotics and serial debridements. Patients who recovered with extensive skin loss underwent skin grafting subsequently with follow-up for 6 months to assess morbidity. Results: Twenty patients with Necrotizing Fasciitis were admitted during study period. Mean age was 57.4 years. Fever, painful swelling, redness, presence of bullae/blistering, skin necrosis and foul smelling discharge were the main clinical findings. Diabetes Mellitus (DM) was the commonest predisposing factor. Sepsis (70%) was the commonest complication. The overall mortality rate was 30% however the most common cause of death was acute Myocardial Infarction (MI). Partial thickness skin grafting was required in 50%. Muscle contractures were noted in 40% patients. Conclusion: Necrotizing Fasciitis, a rare but life threatening condition carries a definite mortality rate. The risk factors for mortality are missed diagnosis, old age, diabetes mellitus and late presentation.